Growth peculiarities of doped lithium dihydrogen phosphate single crystals from nonstoichiometric solution - Iurchenko, A.N.; Voronov, A.P.; Roshal, A.D.; Kryvonogov, S.I.; Babenko, G.N.; Pritula, I.M. (Functional Materials, 2017)
Single crystals of lithium dihydrogen phosphate (LDP) have been grown on a seed by pulling-out from aqueous viscous solutions with an excess of orthophosphoric acid. The effect of solution stoichiometry on the habit and morphology of the faces of LDP single crystals is investigated. It is established that the habit of the crystals changes with the rise of concentration of the acid in the solution. Shown is the effect of dopants of thallium ions, molecules of salicylic and 5-aminosalicylic acid on the morphology of the crystal faces, which manifests itself in a diminution of the width of the terraces and an increase of the density of the growth steps. Proposed is a model of arrangement of the dopant molecules in the interplanar space of LDP crystal lattice.